Implementation of Student Teams Achievement Division Strategy Assisted by Strip Story in Mahārah Kitābah Learning - Misbahul Munir; Aminudin Aminudin (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2026)
Arabic writing (maharah kitābah) instruction in Islamic junior secondary schools continues to encounter challenges, particularly in students' difficulties organizing ideas coherently, applying Arabic grammatical structures accurately, and actively participating in writing activities. These problems are associated with the limited integration of cooperative learning strategies and contextual instructional media. This study aims to analyze the implementation of the Student Teams Achievement Division (STAD) strategy assisted by Strip Story media in maharah kitābah instruction at MTs Jauharatul Islamiyah. The study employed a qualitative case study design involving the principal, an Arabic language teacher, and students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the implementation of STAD assisted by Strip Story was carried out through systematic instructional planning, collaborative group learning, individual assessment, and group recognition. Teacher readiness, heterogeneous grouping, and contextual learning media supported successful implementation, whereas differences in students' Arabic proficiency and limited instructional time became the main challenges. This study contributes to Arabic language pedagogy by providing empirical evidence on the implementation of integrated cooperative learning and contextual media to support maharah kitābah instruction.